An unbalance-based evaluation framework on urban resources and environment carrying capacity. (September 2021) - Zhou, Jingyang; Chang, Shasha; Ma, Wenqiu; Wang, Danyang
Highlights: A systematic review of the current urban RECC evaluation. The unbalanced characteristics of urban development are analyzed. Providing a brand-new conceptual model on urban RECC for meeting the unbalance characteristics when evaluating urban RECC. The division of urban grid units and the introduction of urban RECC finite element analysis. Abstract: The evaluation and optimization of the carrying capacity of urban resources and environment is an important basis for sustainable development of cities and society. The change of urban space scale indicates that serious unbalance crisis of urban space distribution is hidden behind the rapid development. This paper aims to provide a brand-new way for meeting the unbalance characteristics when evaluating carrying capacity of resource and environment. Firstly, an analysis on the unbalance characteristics of urban development was conducted for providing a foundation for this research. Secondly, the thought of urban grid and finite element analysis were introduced to this study. As a result, a conceptual framework was designed for evaluating resources and environment carrying capacity (RECC) under the unbalance condition. This conceptual framework includes four steps, which are construction of basic database, the division of urban grid and the mechanical analysis of RECC, finite element analysis of urban unit grid, and integration of RECC. A detailed introduction of the whole process was provided. The research results will provide an innovative idea for the evaluation of urban RECCs. It can also inspire urban managers to proceed from the status quo and make full use of urban resource and environmental systems.